Long-standing pleomorphic adenoma in hard palate: A rare case report - Hanafiah, Olivia Avriyanti; Dohude, Gostry Aldica; Ayuni HG, Afifah; Tanandika, Janesia; Wirsa, Dinda Andaru (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Pleomorphic adenoma (PA) is the most common benign tumor of the parotid gland, followed by the submandibular gland, and rarely in the minor salivary glands. However, it has the potential to turn malignant. The minor salivary gland in the hard palate is a rare site for PA. Purpose: This report aims to describe the clinical and histopathology findings and treatment with surgical excision of long-standing PA on the hard palate. Case: 40-year-old woman with an asymptomatic 6 x 4 x 4 cm hard palate tumor mass that had remained untreated for ten years and had no preceding trauma. Case Management: The tumor mass was removed surgically by creating an excision opening of 2–3 mm between the mass margin and the maxillary bone periosteum, extending to the posterior palate. Histopathology findings confirmed the diagnosis of PA in the minor salivary gland and revealed typical characteristics associated with malignant transformation. Observation after one month showed that the surgical wound had healed, and no symptoms of recurrence were visible. Conclusion: PA is a benign salivary gland tumor that has the potential to expand extensively. Appropriate surgical excision can improve the prognosis.